INFLUENCES OF RAMAYANA ON RELIGIOUS AND SPIRITUAL PRACTICES IN INDIAN SOCIETY - Dr. Meruprabha Mishra (Samā Jiva Jnānam (International Journal of Social Studies), 2025)
The Ramayana is a revered epic in Indian literature that has profoundly influenced the religious and spiritual fabric of Indian society for centuries. This research paper delves into the various ways the Ramayana affects religious rituals, devotional practices, and spiritual beliefs across diverse regions of India. It also explores the epic's subtle influences on traditions such as Buddhism and Jainism. By synthesizing historical texts, ethnographic studies, and contemporary religious practices, this study seeks to elucidate the Ramayana’s significance as both a literary masterpiece and an essential spiritual guide. It plays a crucial role in shaping moral values, influencing worship patterns, and cultivating community identity. This research aims to deepen the understanding of the epic's enduring legacy and its impact on collective spirituality in India.